The "inclusion-moderation" illusion: re-framing the Islamic movement inside Israel. Issue 4 (19th May 2021) - Larkin, Craig; Nasasra, Mansour
ABSTRACT: The inclusion-moderation thesis posits that radical movements can be moderated through participation in democratic pluralist politics. Repeatedly applied to Islamist movements questions remain over its conceptual ambiguity and empirical veracity. Despite such weaknesses this thesis continues to be utilized to explain the diverging trajectories of the Islamic movement within Israel – its Southern accommodationist parliamentary branch (IMSB) and its separatist Northern branch (IMNB), now officially banned by Israel. This article examines this significant yet understudied movement, as a means of challenging the reductionist reading of Arab Islamist politics in Israel while at the same time rethinking the perimeters of inclusion-moderation theory. The case suggests that Islamist strategic moderation may be a result of both state repression and political inclusion but rarely does it lead to complete ideological transformation. This research suggests the IMSB's pragmatic evolution, owes less to Knesset participation and more to internal organizational debate, a convergence of broader Arab-Israeli positions, and a response to the failings of post Arab Spring Islamist politics. Conversely, the IMNB's perceived radicalism, is less to do with its extreme ideology but rather its own strategic framing and Israel's ongoing fears of the mobilizing potential of Al-Aqsa mosque.